The Sixth Sector Industrialization of Agriculture and the Relay Shipping of Vegetables in Japan: Implications for the Agricultural and Rural Development of Middle Income Countries - Yonekura, Hitoshi (Advances in Social Sciences Research Journal, 2021)
This paper aims to extract lesson from the experiences of Japan for escaping from the middle income trap which many countries in Asia and Africa confront. This paper will review in detail the efforts to increase the income levels of rural and agricultural firms by establishing a value chain under an almost zero growth economy in the 2000s in Japan. After referring to the condition of Japan agriculture and the framework of structural reform of agricultural policy of Japan, the core action schemes of the Sixth Industrialization and Relay Shipping are focused on. The mechanisms of relay shipping of vegetables and the institutions for facilitating the scheme are reviewed in detail. It is revealed that institutional capacity for greater inter-sector and government coordination are essential for implementing the schemes to establish effective and efficient value chain. These are institutional reform and capacity building efforts in Japan. Experiences in Japan reveal that various executing agencies with good governance are required to establish the mechanism of effective resource mobilization and implement reform of value chain. There have been no detail studies on implementing such reform for establishing sustainable value chain in countries where escaping middle income trap is needed. This study should be useful lesson for countries confronting the middle income trap.